Load Frequency Control of Interconnected Hydro-Thermal System with Conventional Controllers and Expert Controllers - Krishan Arora; Baljinder Singh (Institute of Advanced Engineering and Science, 2012)
Load-frequency control (LFC) is a part of the Automatic Generation Control (AGC) in power systems, the aim of which is to maintain the system frequency and tie line flow at their scheduled values during normal period in an interconnected system. This research paper is devoted to explore the interconnection of the load frequency control of hydro power system and the thermal system. The thermal system is comprised with governor dead band, generation rate constraint and boiler dynamics where as the hydro system is comprised with generation rate constraint. The conventional PID controller does not have adequate control performance with the consideration of nonlinearities and boiler dynamics. To overcome this drawback, Genetic Algorithm helps in solving optimization problems by exploitation of random search. The aim of the proposed expert controller is to restore the frequency to its nominal value in the smallest possible time whenever there is any change in the load demand etc.